The changes in agriculture land use in Kuala Krai before and after flood inundation - Matan Ibrahim, Matan Iskandar (2016)
At the end of each year in the East Coast of Malaysia the monsoon season occurs. There will be high volume of rainfall that leads to flood in certain areas of the East coast. The worst flooded and affected area in 2014 is Kuala Krai which caused lots of lost lives and houses. The flood has risen about 3-storey high. People found shelter at high buildings such as schools, hills and the hospital. Increasing human activity downstream and upstream of the river system results in greater flood damage in terms of size and frequency. It has caused the stream to become shallower year after year and resulted in flood when there is high volume of rainfall in that area. Two main reasons for the unprecedented flooding magnitude are the changing climatic patterns that cause adverse weather effects and uncontrolled land management that increased exploitation of land resources. Hence, the aim of this study is to assess the effect of flood severity on area of agriculture land use in Kuala Krai, Kelantan. The land use change analysis in the study is undertaken using the Geographical Information System (GIS). The land use is classified into 5 categories based on Anderson et al. (1976) scheme which are agriculture area, forest, open area, urban area and water.